2012
DOI: 10.1186/1471-2091-13-17
|View full text |Cite
|
Sign up to set email alerts
|

The role of molecular chaperonins in warm ischemia and reperfusion injury in the steatotic liver: A proteomic study

Abstract: BackgroundThe molecular basis of the increased susceptibility of steatotic livers to warm ischemia/reperfusion (I/R) injury during transplantation remains undefined. Animal model for warm I/R injury was induced in obese Zucker rats. Lean Zucker rats provided controls. Two dimensional differential gel electrophoresis was performed with liver protein extracts. Protein features with significant abundance ratios (p < 0.01) between the two cohorts were selected and analyzed with HPLC/MS. Proteins were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In addition to the regular function of HSP in folding and unfolding proteins, induction of its expression in response to stress has been suggested to be protective for the cells (18,19). A proteomic analysis showed that the blockage of chaperones such as HSP may contribute to increased rates of apoptosis and necrosis (20). Hence, we investigated the roles of HSP in response to hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regular function of HSP in folding and unfolding proteins, induction of its expression in response to stress has been suggested to be protective for the cells (18,19). A proteomic analysis showed that the blockage of chaperones such as HSP may contribute to increased rates of apoptosis and necrosis (20). Hence, we investigated the roles of HSP in response to hepatocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies recollected both ischemia and reperfusion samples and compared them to control (pre- ischemia) samples and even between them (18,29,36). When rats were used as a model, Knecht et al (16) carried out ex vivo cold storage and normothermic reperfusion, whereas the other 2 publications performed a model of in vivo selective warm ischemia using vascular clamping followed by reperfusion, such in normal (20) as in steatotic rats (27).…”
Section: Sample Sources and Study Typesmentioning
confidence: 99%
“…Tiriveedhi et al have demonstrated that even the proteome profiles of livers with steatosis subjected to IRI, are significantly different compared to lean livers (23).…”
Section: Pathophysiological Changesmentioning
confidence: 99%
“…by Tiriveedhi et al has shown significant down-regulation of multiple chaperones upon IRI in steatotic liver, which may contribute to the augmented levels of ER stress and, subsequently, in apoptosis and necrosis observed in livers with steatosis, in contrast to lean ones(78). However, Henkel et al, have shown that chemical chaperones inhibit the ER stress response without reducing hepatic steatosis in MCD diet-fed mice(76).Selectins.…”
mentioning
confidence: 99%